PENGARUH CUSTOMER DELIGHT (JUSTICE, ESTEEM DAN FINISHING TOUCH) TERHADAP ACTIVE DAN PASSIVE LOYALTY - Meliza Dwi Ratna Sari; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to discuss and analyze the influence of customer delight: justice, esteem and finishing touch on active and passive loyalty. The population consisted of 221 and a sample of 70 respondents. Data collection in this study used a questionnaire. Data analysis in this study used SPSS 14. Application data used in this study included multiple linear regression analysis, validity test, reliability test, normality test, classic assumption test and hypothesis test. That there are simultaneous effects of variables of justice, esteem and finishing touch on the active and passive loyalty of Primagama's tutoring institutions. Partially customer delight, namely the esteem variable, has no significant effect on the variable active and passive loyalty of Primagama's tutoring institution. Whereas the justice and finishing touch variables have a significant influence on the variable active and passive loyalty of Primagama's tutoring institution.Keywords:Customer Delight; Justice;Esteem;Finishing Touch;Active Loyalty;Passive Loyalty